Characteristics of winter durum wheat varieties according to gluten-protein complex of grain - О. A. Kostylenko; N. G. Ignatieva; N. S. Kravchenko; А. S. Ivanisova (Зерновое хозяйство России)
The high demands to the quality of Triticum durum grain place by modern pasta processing plants dictate the need to use additional methods and approaches to estimating breeding material and selecting high-quality genotypes. The purpose of the current study was to identify sources of valuable traits of winter durum wheat for targeted inclusion in breeding programs to develop varieties with strong gluten. Field trials were conducted in the laboratory for breeding and seed production of winter durum wheat of the FSBSI “ARC “Donskoy” in 2022–2024. Laboratory study was conducted in the laboratory of biochemical and technological estimation in accordance with the methods and GOSTs. The material for the study was a set of the varieties of the inter-station variety testing (n = 36). The variety ‘Kristella’ was used as a standard. As a result of the study, there were identified the varieties as the sources of high protein and gluten percentage. There were also identified the varieties with high gluten quality according to SDS sedimentation, IDC, and gluten index. There was found that the gluten index limited the gluten quality. There were identified the varieties ‘Diona’ and ‘Gavan’ with strong gluten. There have been presented the results of the correlation between grain quality traits. There have been established the most accessible informatively significant traits such as protein percentage, gluten quantity and quality (IDC), SDS-sedimentation, gluten index, which have a decisive effect on gluten strength and can be used as breeding criteria in the breeding process, including at early stages.